(untitled) (Damascus University Journal for legal sciences, 2024)
The soundness of the national economy and the effectiveness of the monetary policy of any country depends on the soundness of the financial and monetary system, and in particular the soundness of the banking sector as one of the main pillars of the monetary system, as banks collect national savings and repurpose them in the service of national economic activities. various sectors with the necessary funding to carry out their activities, and provide banking services of all kinds. It is necessary to subject this sector to the oversight process whose responsibility lies mainly with the Central Bank, in order to maintain the integrity of the financial positions of the banks, and to reach a sound banking sector that preserves the rights of depositors and investors, and ensures the proper implementation of the state’s monetary policy in an appropriate manner, in a manner that ensures the contribution in an appropriate manner, Effective in the development and prosperity of the national economy. In this research, will be addressed the importance of the supervisory role of the Central Bank of Syria over other Syrian banks, especially in light of the economic crisis that Syria has been experiencing from 2011 to date.